EFEKTIVITAS KINERJA JURUSITA PAJAK DALAM MELAKUKAN PENAGIHAN PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA MANADO DAN KANTOR PELAYANAN PAJAK PRATAMA BITUNG - Afrilia, Megi; Sondakh, Jullie J.; Lambey, Robert (Universitas Sam Ratulangi, 2016)
In the effort of securing national revenue the work of Tax Bailiff is needed, for if everything is delegated to the Tax Payer, then the achievement of targets could not be guaranted. When making tax collection, performance of Tax Bailiff are affected by various things: limited numbers of Tax Bailiff, unkown address of the Tax Payers or Tax Guarantors, and more. The purpose of this study is to determine the level of performance evectiveness of the Tax Bailiff when making tax collection at Manado Tax Office and Bitung Tax Office. The research needs quantitative data, uses primary data, and uses descriptive analysis research method.The result indicates the level of performance evectiveness of Tax Bailiff by the year of 2014 at Manado Tax Office are 56,82% (non-efective), while Bitung Tax Office are 47,83% (non-evective). The level of performance evectiveness of Tax Bailiff by the year of 2015 at Manado Tax Office are 51,37% (non-evective), while Bitung Tax Office are 63,52% (less-evective). Keywords: Tax Collecting, Tax Bailiff, Tax Due.